Indicators of physical fitness in school children from the midwest region of São Paulo City - Maria Tereza Silveira Böhme; Alessandro H. Nicolai Ré; Carla Nascimento Luguetti (Universidade Federal de Santa Catarina, 2010)
The objectives of this study were: a) to evaluate indicators of physical fitness in childrenand adolescents according to chronological age and gender; b) to classify their performanceusing the PROESP-BR normative tables. A total of 3145 randomly selected school children (1590boys and 1555 girls), ranging in age from 7 to 16 years, were submitted to the following tests:distance covered in a 9-minute run, standing long jump test, medicine-ball throw, and 60-s situptest to measure abdominal muscle endurance. Significant differences were observed betweengenders at all chronological ages and also between boys of different chronological ages. In girls,no significant differences were observed between chronological ages, with performance tendingto stabilize at 11/12 years of age. Classification of the participants according to the PROESP-BRnormative tables showed that more than 50% of all subjects were below the 40th percentile in alltests, especially girls. The same tendency was observed when compared to other Brazilian studies.Considering mean values, it can be concluded that the school children studied, especially girls,presented a low level of physical fitness, thus indicating the need for health promotion programsin the midwest region of São Paulo City addressing physical activity.